2017
DOI: 10.1186/s12910-017-0197-6
|View full text |Cite
|
Sign up to set email alerts
|

Are advance directives helpful for good end of life decision making: a cross sectional survey of health professionals

Abstract: BackgroundThis paper joins the debate over changes in the role of health professionals when applying advance directives to manage the decision-making process at the end of life care. Issues in relation to advance directives occur in clinical units in Lithuania; however, it remains one of the few countries in the European Union (EU) where the discussion on advance directives is not included in the health-care policy-making agenda. To encourage the discussion of advance directives, a study was designed to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 24 publications
2
23
0
11
Order By: Relevance
“…This large difference can be associated to the curricular approach of the courses. The results are similar to those of the present study: only 24.6% of physicians fully understand the definition of AWD 17 . In other studies, there is also a lack of knowledge about the subject in the population as a whole: 94,5% of patients did not know anything about LW 13 .…”
Section: Discussionsupporting
confidence: 91%
“…This large difference can be associated to the curricular approach of the courses. The results are similar to those of the present study: only 24.6% of physicians fully understand the definition of AWD 17 . In other studies, there is also a lack of knowledge about the subject in the population as a whole: 94,5% of patients did not know anything about LW 13 .…”
Section: Discussionsupporting
confidence: 91%
“…중환자실의 경우, 사망가능성이 높은 환자의 입실로 연명의료의 시작이나 중단 등과 관련하여 환자나 보호자 등이 의사결정해야 하는 상황이 빈번하게 발생된다 (Coffey et al, 2016;. 실제로 중환자실에 입원하는 환자 의 약 6~11%가 연명의료를 받고 있고, 중환자실에서 발생하는 사망의 50~90%가 연명의료 중단과 관련이 있다고 알려져 있다 (Opgenorth et al, 2018 (Moon, 2015;Myburgh et al, 2016;Peicius, Blazeviciene, & Kaminskas, 2017). 중환자실은 주로, 급성 중증 환자들을 치료하는데 목 적을 두고 있으며, 고도의 기술적, 치료적인 관점에 중 점을 두고 있어 생애말 환자간호에 대한 관심은 상대적 으로 부족한 실정이다 Moon, 2015 (Chan et al, 2019;Jimenez et al, 2018;Saloron, Ramos, Schnelder, da Silveira, & Silveira, 2017;Vuong, Kittelson, McCullough, Yingwei, & Hartjes, 2019 (Han, Chung, Moon, Han, & Ko, 2001 [18]; Bae et al, 2009 [A14]; Revised by author [A4])…”
Section: 연명의료란 회복 불가능한 말기 환자에게 주 질환에unclassified
“…Care planning for EOL is a means to bridge gaps in health care delivery and empower self-determination and promotion of self-care actions among patients. 12,13 The estimated percentage of older adults who have executed an advance directive has been estimated at between 55% and 60% for older adults who reside in the community. 14 A compelling reason explaining this fairly low percentage is the low levels of knowledge of EOL care plans among older adult populations and health care providers.…”
Section: Background and Importance Of This Studymentioning
confidence: 99%
“…14 A compelling reason explaining this fairly low percentage is the low levels of knowledge of EOL care plans among older adult populations and health care providers. 12,15,16 Limited studies have examined older adults' perceptions of selfcare actions related to EOL planning for its importance level and their desire and ability to perform these actions. 4,5,17 One recent US study found that adults' perceptions of self-care actions are associated with their self-reported health outcome (ie, emergency room use in the past 3 months).…”
Section: Background and Importance Of This Studymentioning
confidence: 99%
See 1 more Smart Citation